RISK OF THE IGNITION OF FLUID FUELS AND SOAKED MATERIALS DURING OXYACETYLENE CUTTING OF METALS - V. Vladimirov, Lyubomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The purpose of this study is to establish the regularities of the process of firing of liquid fuels and materials, soaked with liquid fuels, during oxyacetylene cutting. By means of suitable methods and a plant, we studied the firing of petrol and diesel fuel and paper, textile and wood chips, soaked with fuel. Three basic tasks have been solved – physical modeling of dangerous event and dangerous action, determination of danger indexes and assessment of firing in the zone of distribution of waste metal spatters. Regression models of probability and time of firing depending on the distance, height and materials subject to cutting and other factors have been formulated.